UJI AKTIVITAS ANTIBAKTERI SEDIAAN GEL EKSTRAK DAUN BELIMBING MANIS (Averrhoa carambola L.)TERHADAP Staphylococcus epidermidis - Indriani Dini Mustava; Gigih Kenanga Sari; Supriyanto (Joseph: Journal of Science and Pharmacy, 2025)
Background: A major factor in the development of acne is bacterial activity within infected hair follicles. One of the bacteria involved in acne formation is Staphylococcus epidermidis. Star fruit leaf extract (Averrhoa carambola L.) contains alkaloids, flavonoids, tannins, triterpenoids, and saponins, which can act as antibacterial agents. Purpose: This study aims to formulate gel preparations of star fruit leaf extract (Averrhoa carambola L.) at concentrations of 3%, 4%, and 5%, and to evaluate their antibacterial activity against Staphylococcus epidermidis. Method: Star fruit leaves were extracted using the maceration method with 70% ethanol. The extract was formulated into gel preparations at concentrations of 3%, 4%, and 5%, followed by antibacterial activity testing against Staphylococcus epidermidis using the well diffusion method. Results: The study showed that the star fruit leaf extract (Averrhoa carambola L.) contains alkaloids, flavonoids, saponins, tannins, and triterpenoids. The gel formulations exhibited antibacterial activity with inhibition zones of 8,61 mm, 9.48 mm, and 11,50 mm for the 3%, 4%, and 5% concentrations, respectively. Conclusion: The gel preparation of star fruit leaf extract (Averrhoa carambola L.) with the highest antibacterial activity was the Formula 3 gel containing 5% extract